New taphonomic approach applied to the Late Pleistocene bone remains from Pikimachay Cave, Ayacucho Basin, Peru: possible implications for the debate on human colonisation of western South America - Hugo G Nami; Karina V Chichkoyan; Juan Yataco Capcha; José L Lanata (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
The Pikimachay cave in south-eastern Peru had an important role in archaeological discussions concerning the first peopling of South America, and the Southern Andes in particular. The excavations by Richard MacNeish in 1969-1970 identified a sequence of possible but controversial Late Pleistocene human occupations up to historical times. As a part of a research programme aiming to re-assess the Late Pleistocene remains from this site, we made taphonomic observations on a sample of bones (n=40) from the lower strata (layers h to k) as follows: h (n=17), h1 (n=6), i (n=4), i1 (n=7), j (n=5), and k (n=1). The conventional uncalibrated radiocarbon dates initially obtained suggest that these layers span a period of ~14.0 to 25.0 thousand years before present (kybp). Each bone was thoroughly examined to determine the nature of modifications to them, and to describe alterations and the general condition of the specimens in order to identify possible anthropic intervention. For this purpose, we examined the surface modifications indicating fresh or post-depositional fractures, the different kinds of marks, weathering, and the presence of manganese staining. We concluded that several bones (n=8) from layer h showed various human-made modifications. We can therefore suggest that this new information justifies the assumption that the bones and lithic materials from layer h would have been produced during the Early Holocene/Late Pleistocene between ~≥9.0/10.0 and ~14.1, probably at ~14.1 kybp; an assumption that can also be considered for the stone remains from the underlying strata h1 that yielded a similar date. The bone remains from strata j to k do not show any human modifications. Furthermore, if the reported chronology and its association with the anthropic remains are true, the Pikimachay cave could still be relevant to the debate over the human colonisation of western South America that occurred within a similar timeframe during the postglacial era.